Opioid-related harms and experiences of care among people in justice settings in New South Wales, Australia: evidence from the National Ambulance Surveillance System - Naomi Beard; Michael McGrath; Harry M. X. Lai; James Wilson; Anthony Hew; Amaya Muñoz Labiano; Dan I. Lubman; Rowan P. Ogeil (Harm Reduction Journal, 2025)
Abstract Background People in justice settings experience higher rates of psychiatric morbidity, including alcohol and drug use disorders, compared with the general population. However, our understanding of opioid-related harms in justice settings is limited. This study used ambulance data to examine opioid-related harms and experiences of care in New South Wales (NSW), Australia, during periods of incarceration or detention. Methods This mixed-methods study used data from the National Ambulance Surveillance System (NASS) for patients aged 18 and older with an opioid-related ambulance attendance between December 2020 and April 2023. People in justice settings were identified using ambulance billing codes and manual review of paramedic case notes. Descriptive statistics described the patterns and modalities of opioid-related harms in justice settings, and a qualitative thematic analysis of paramedic case notes was used to contextualise findings. Results Over the study period, 328 opioid-related ambulance attendances for people in justice settings were identified (51% heroin; 41% opioid agonist therapy (OAT) medication). Symptoms of opioid withdrawal were noted in 35% of attendances, most commonly for heroin (51%) and withdrawal from OAT medications (48%). Three interconnected themes were identified using qualitative analysis: trust and mistrust in justice settings, systemic barriers to providing OAT, and other harm reduction strategies, and experiences of withdrawal in justice settings. Conclusion Our study demonstrated the utility of ambulance data in identifying opioid-related harms for people in justice settings in NSW. Qualitative findings highlight current barriers to effective opioid care in justice settings and identify opportunities for intervention, including targeted harm reduction programs, as well as policies that promote continuity of care particularly during transitions in and out of justice settings.